2014
DOI: 10.1155/2014/631709
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate-Induced Periprosthetic Fracture: A Cause of Painful Total Hip Arthroplasty

Abstract: Background. Cases have been reported in the literature of periprosthetic fractures associated with the use of bisphosphonates occurring in the long term following a Total Hip Replacement (THR). We report an interesting case of periprosthetic fracture secondary to bisphosphonate use only a few months after a THR. Case Report. A 72-year-old lady (on bisphosphonates for 10 years) underwent a THR for osteoarthritis. She was pain-free in the first four months postoperatively. Thereafter, she developed spontaneous o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…callus and disappearing fracture line at 4 months postoperatively, and the patient was able to walk without assistance or thigh pain. Similar cases have been reported (Table 1) [3][4][5][6][7][8][9][10][11][12]. All were females and all had a history of long-term bisphosphonate therapy.…”
Section: D B a B Asupporting
confidence: 77%
“…callus and disappearing fracture line at 4 months postoperatively, and the patient was able to walk without assistance or thigh pain. Similar cases have been reported (Table 1) [3][4][5][6][7][8][9][10][11][12]. All were females and all had a history of long-term bisphosphonate therapy.…”
Section: D B a B Asupporting
confidence: 77%
“…Curtin et al reported three cases of incomplete PAFFs treated by discontinuing BPs and limiting weight bearing; later, teriparatide was added to two cases [ 3 ]. Cross et al reported incomplete PAFFs treated by discontinuing BPs, starting teriparatide, and limiting weight bearing [ 4 ], while Bhattacharyya et al reported successful treatment of incomplete PAFFs by only discontinuing BPs and limiting weight bearing [ 8 ]. Lee et al reported preventive osteosynthesis surgery performed for a case in which femoral pain and fracture lines were revealed despite loading restriction and teriparatide administration for incomplete PAFFs [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their action in preventing fragility fractures can cause a hip's range of motion alteration in a few patients. This can cause micro fractures especially in more mechanical stress sites as the lateral femoral cortex (12,13). In hip prosthesis the femoral stem presence, changing the bone modulus of elasticity, can increase the amount of mechanical stress and promote the occurrence of femoral atypical fractures.…”
Section: Discussionmentioning
confidence: 99%